Transitive and intransitive verbs in English language - Umurova Mohinur, Mukhamadiyev Aziz Shavkatovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
Essential to the construction of coherent sentences, transitive and intransitive verbs are basic building blocks of English grammar. A direct object, which responds to the queries "what?" and "whom?" following the verb, is necessary for transitive verbs to fully express their meaning. In "She reads a book," for instance, "reads" is the transitive verb and "a book" is its direct object. When communicating whole events or states, intransitive verbs, on the other hand, do not require a direct object in order to function. As an illustration, "He sleeps" makes use of the intransitive verb "sleeps" without requiring any other context. According to how they are used in a sentence, some verbs can be either transitive or intransitive. An example of this dual functionality is "She runs a company" versus "She runs every morning". Since it helps with creating syntactically accurate sentences and avoiding common mistakes, this knowledge is very helpful for language learners and anyone looking to improve their grammar skills. Understanding the ways in which transitive and intransitive verbs add to the diversity and complexity of the English language can be better understood by examining a range of instances and settings.